A New Strategy to Improve the Performance of Informed RRT* Algorithm in Solving the Global Path Planning of Mobile Robot - Suwoyo, Heru; Winiyoga, January Dwidasa; Andika, Julpri (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
Informed RRT* has been mentioned as a great method to find feasible and optimal solution of path planning. Technically, it uses the prolate hyper-spheroid and a centralized optimization strategy to gain the optimality of path. This optimization process is started when the initial feasible solution is found. Conventionally, the traditional procedure of RRT* is used to connecting starting point and goal point feasibly. Therefore, it is not suppressing if the optimization process begins later in large coverage of path planning problem. For this reason, a new strategy needs to propose with an objective to speed up the convergence rate by reducing the inefficiency of its blind sampling. Sequentially, it is conducted by integrating the bias technique and constraint sampling to replace the traditional sampling method. Next, the nearest node's ancestor is taken into consideration up until the first stage of choosing the parent is less expensive then RRT*. Regarding to these offers and the comparative results, the performance of the proposed method has shown better performance compared to its predecessor in terms of optimality, indicated by a decrease in finding the initial path by an average acceleration of 47.90% and a convergence rate indicated by an average path cost decrease value of 3.94%.